Implementation of Employee Remuneration Policy After Change of Status University of Brawijaya to PTNBH - Susita, Erma Lia; Rochmah, Siti; Hayat, Ainul (Wacana Journal of Social and Humanity Studies, 2023)
University of Brawijaya (UB) is a public service organization. UB in terms of implementing remuneration based on position and class of position. The civil servant remuneration system must adhere to the performance system, namely determining the amount of performance allowance, work weight, and grade for each position. The purpose of this study is to identify, describe, and analyze the implementation of remuneration policies that will be implemented at the University of Brawijaya, especially in the Directorate of Administration and Academic Services after the change in status of Brawijaya University to Perguruan Tinggi Badan Hukum. This research is a type of descriptive research with a qualitative approach. This research uses Edward III's Theory on Communication and Resources to assess remuneration policy implementation. The results of this study in terms of communication, the communication strategy carried out in conveying information on policy implementation from the leadership to the organizational structure below is carried out to the UB remun team in the hope that the UB remun team disseminates the information to employees in each unit and it turns out that the strategy This communication has not run optimally with the goals and objectives by the policies made. Resources that have supported each other in implementing remuneration policies in UB after UB became PTNBH. Keywords: implementation, employee remuneration, reward, Edward III